Examining the impacts of conventional exports on GVC participation: Evidence from developing economies - Rafique, Kalsoom (Journal of Accounting, Business and Finance Research, 2025)
International trade is under dramatic changes, and production processes gradually involve a sequential, vertical trading chain extending across the borders of various countries. Each country specializes in a certain stage of production. The study aims to examine the impacts of conventional exports to China on participation in global value chains during 1992-2019 for developing countries. This study used an instrument variable method to analyze developing countries’ GVC participation and export responses to China’s massive demand shocks. The export flow of other developing countries to China is used as an instrument variable for analyzing the changes in GVC participation of sample countries’ exports. The findings of the study reveal that the rise of China in the global economy caused significant gains in developing countries, both in participation in GVCs and exports. In the aggregate, the sample developing countries have caused some averaged 0.33% increase in the GVCs participation from 1992-2019, while their exports to China had an average annual growth of 3% over the same period, which indicates the importance of the relationship between GVCs and conventional exports. The growth rate of exports also suggests that China is an attractive export destination for developing countries, and these countries need to develop strong ties with China, as well as a large economy and consumer market.